Effects of SiC Nanoparticle Content on the Microstructure and Tensile Mechanical Properties of Ultrafine Grained AA6063-SiCnp Nanocomposites Fabricated by Powder Metallurgy. Issue 9 (September 2017) - Yao, X.; Zhang, Z.; Zheng, Y.F.; Kong, C.; Quadir, M.Z.; Liang, J.M.; Chen, Y.H.; Munroe, P.; Zhang, D.L.
Abstract : Ultrafine grained AA6063-SiCnp nanocomposites with 1, 5 and 10 vol.% SiCnp have been fabricated by a novel powder metallurgy process. This process combines high energy ball milling of a mixture of 6063 alloy granules made from machining chips and SiC nanoparticles and thermomechanical powder consolidation by spark plasma sintering and hot extrusion. The microstructure and tensile mechanical properties of the samples were investigated in detail. Increasing the SiC nanoparticle content from 1 to 10 vol.%, the yield strength and ultimate tensile strength increased from 296 and 343 MPa to 545 and 603 MPa respectively, and the elongation to fracture decreased from 10.0%, to 2.3%. As expected, a higher SiC nanoparticle content generates a stronger inhibiting effect to grain growth during the thermomechanical powder consolidation process. Analysis of the contributions of various strengthening mechanisms shows that a higher SiC nanoparticle content leads to a higher contribution from nanoparticle strengthening, but grain boundary strengthening still makes the largest contribution to the strength of the nanocomposite. When the SiC nanoparticle content increased to 10 vol.%, the failure of the nanocomposite was initiated at weakly-bonded interparticle boundaries (IPBs), indicating that with a high flow stress during tensile deformation, the failure of the material is more sensitive to the presence of weakly-bonded IPBs.